Peran Guru Kejuruan Bidang Pertanian dalam Mempersiapkan Generasi Emas - Rojaki, Much; Yuliana, Belvi; Waluyo, Ribut (Universitas Islam Sultan Agung, 2024)
This article examines specifically the role of vocational teachers in the field of agriculture in preparing the golden generation. The agricultural sector plays an important role in life but is becoming increasingly less popular among the younger generation as its successors. Vocational teachers in the field of agriculture are the spearhead in developing agricultural human resources in the world of education. This research methodology uses a qualitative approach with the data collection techniques used are observation and interviews where the resource person is a vocational teacher in the field of agriculture. Based on research results, the role of vocational teachers includes acting as a fosterer of student interest, parents at school, career guidance and counselling, professional developer, fosterer of entrepreneurial spirit and collaborator with the world of work and industry. Conclusion: The role of vocational teachers in agriculture is very important in preparing students to enter the workforce as Indonesian agricultural human resources